The Relational Self Revealed Integrative Conceptualization and Implications for Interpersonal Life. [article]. - Chen, Serena
The authors offer a new, integrative of the relational self based on a synthesis of recent approaches to the se a sharper and fuller definition of the relational self than does any existing approach alone and a common framework to interpret findings from separate literatures. The authors then present 5 propositions and evidence to support the thesis that relational selves exert a pervasive influence on interpersonal life. Specifically, relational selves (a) shape a wide range of psychological processes annd outcomes, (b) exert their influence automatically, (c) serve basic orientayion and meaning functions, (d) provide continuity and context-specific variability, and (e) carry implications for psychological well-being. Discussion focuses on remaining issues and implications for future research. -- (from the author)